Sensors and microsystems AISEM 2010 Proceedings - Neri, Giovanni; Donato, Nicola; d'Amico, Arnaldo; Di Natale, Corrado (Lecture Notes in Electrical Engineering, 2011)
This book contains a selection of papers presented at the 15th Italian Conference on Sensors and Microsystems. It provides a unique perspective on the research and development of sensors, microsystems and related technologies in Italy. In an interdisciplinary approach is taken covering topics, ranging from materials science, chemistry, applied physics, electronic engineering and biotechnologies.